APLIKASI BERBASIS MEDIA PEMBELAJARAN INTERAKTIF SEBAGAI MODEL KOPING UNTUK MENGATASI STRES BELAJAR MATEMATIKA PADA SISWA SEKOLAH DASAR PADA MASA PANDEMI COVID-19 - Lucy Hariadi; Jutono Gondohanindijo (Delta: Jurnal Ilmiah Pendidikan Matematika, 2022)
This study aims to develop a fun interactive learning method as an effort to reduce stress due to online learning, especially in Mathematics. The research was conducted on online fifth grade elementary school students. This Powtoon and Adobe Flash-based learning media application can be accessed from cellphones or laptops. The data collection method used in this research is the experimental method. Statistical calculations obtained the results: (1) there was a difference in the mathematical value between before and after being given treatment as indicated by the value of sig = 0.000 (p < 1%), where there was an increase in the mathematical value from an average of 78.53 to 89.41; (2) there is a difference in the level of stress in students between before and after being given treatment as indicated by the value of sig = 0.000 (p < 1%), with the mean value of 47.44 dropping to 39.85 after being given treatment; (3) there is a significant correlation between stress levels and students' Mathematics test scores before treatment, which is indicated by the value of sig = 0.011 (p < 5%). The direction of the correlation is negative with the value of rxy = -0.429; (4) there is a significant correlation between stress levels and students' test scores in post-treatment Mathematics, indicated by the value of sig = 0.038 (p < 5%). The direction of the correlation is negative with the value of rxy = -0.357. Negative correlation means that the higher the stress felt by students, the lower the learning achievement obtained, and vice versa. Evaluation of the learning application was carried out descriptively and satisfactory results were obtained.